The Great Themes of the Qur'an: By Jacques Jomier. London: SCM Press Ltd, 1997. (American Journal of Islam and Society, 2000)
Jacques Jomier states that this book was written at the request of some nonMuslimsliving and working in the Muslim world, who were daunted by theseemingly "impenetrable" and "closed" nature of the Qur'an - a statementthat is rather surprising when one considers that, for several decades now, contactwith the Qur'an has made Islam the fastest growing religion in the Westernworld. Note especially the author's statement that "Islam is the Qur'an" andthat, according to Christian estimates, Islam will be more practiced in Britainthan Christianity by the year 2006.A superficial glance at the text gives the reader the impression that this is anobjective piece of work, but on closer examination the author's preconceptionsand personal bias become obvious. In the introduction, for example, Jomierdescribes his colleagues - the non-Muslims living with Muslims, for whomthe book is intended - as having "persevered with their project" (p. ix), andthat ''before the present work was written, it was explored and discussed in twoor three closed groups and many of the observations it contains were suggestedby this experience" (p. x). He also defines their strategy in both a patronizingand an evangelical tone, saying, "We will succeed only if we are preparedto listen to them [Muslims] tactfully, without taking their positions as hard andfast, knowing that there are different tendencies among them that are capableof development" (p. xi) ...